Transformasi bagi Seorang Peziarah: Sebuah Pertemuan antara Theologia Viatorum dari Tradisi Reformed dan Fenomenologi dari Emmanuel Falque - Stephen Rehmalem Eliata (Indonesian Journal of Theology, 2022)
The development of theology and of philosophy since the 20th-century has failed to form a harmonious relationship between these domains. The concept of Reformed Epistemology (RE), which attempts from the Reformed tradition to link the two, evinces this failure in that RE unwittingly discredits nature and begets religious fundamentalism. Implications of this arrested development are manifest amid various crises—ecological, social, cultural, and economic. Taking these problematics as a point of departure, the author intends to bridge theology and philosophy by means of retrieving from 17th-century Reformed tradition a theologia viatorum. In connection with the phenomenological philosophy of Emmanuel Falque, the author posits that the proper bridging of theology and philosophy as fields of knowledge will create a harmonious relationship between them and thereby bring about Christian transformation for those called pilgrim (viator). Through such transformation, every Christian might come to realize the final end of theology, which—according to the Reformed tradition—is to worship and glorify God within the world.